LENTIL TANNIN-GLOBULIN INTERACTIONAND AND IN VITRO HYDROLYSIS - NEVES,Valdir A. (1998)
Protein fractions were isolated from lentil cotyledons and tannins were isolated and purified from lentil seed coats. The globulin fraction corresponded to 42.7% of the total lentil flour nitrogen, representing the major protein fraction. Acetone:water (7:3) was the best extractant for seed coat tannins compared to methanol or methanol-HCl 1%. Native and heated (99oC/15 min.) isolated lentil globulin and casein were hydrolyzed with trypsin and pepsin in the absence of tannins and at 1:40, 1:20, 1:10, 1:5 and 1:2.5 tannin-to-protein ratios. The tryptic and peptic hydrolysis of the unheated proteins were reduced with increasing tannin-to-protein ratios. Unheated casein showed to be more susceptible to trypsin than globulin and the opposite effect was observed with pepsin. Heating followed by tannin interaction and hydrolysis had a more pronounced effect on tryptic than peptic digestion for both proteins.